DINAMIKA GENDER DALAM MASYARAKAT - Saguni, Fatimah (Musawa: Journal for Gender Studies, 2020)
The status and roles of women produce various conclusions due to different perspectives and approaches in examining gender relations and the dynamics of interactions that occur in gender relations in society. Biological differences between men and women have occurred since the conception, embryological development and puberty. Socioculturally, these differences are developed in accordance with the conditions that occur among the ethnic groups concerned. This shift can be seen in the increasing number of women who penetrate the public sphere, even willing to leave their homes to get work. Differences in gender roles that are formed by society are continuously socialized through education, either directly or indirectly in families, schools and in the community. Therefore, society really adheres to the rules that differentiate the roles of women and men. For this reason, various efforts are needed to fight for gender equality in people’s lives.